Serial haemoglobin measures after acute coronary syndrome: a strong, simple and independent predictor of long-term cardiovascular outcome. (22nd September 2015) - Ang, DSC; Kao, MPC; Lang, CC; Struthers, AD
Abstract : Introduction: Baseline anaemia in patients with acute coronary syndrome (ACS) is an independent predictor of adverse clinical outcomes. However, little is known about serial haemoglobin measures after an ACS event and its impact on prognosis in this patient population. We sought to determine the prevalence and prognostic impact of anaemia (based on WHO criteria) at baseline and at 7 weeks follow-up in consecutive ACS patients. Methods: Haemoglobin levels were measured in 448 consecutive patients presenting with ACS and at 7 weeks outpatient follow-up. The main outcome measure was either the occurrence of death or acute myocardial infarction (AMI) over a median duration of 2.5 years (range 1–50 months). Results: Of the 448 patients, 120 patients presented with ST elevation myocardial infarction (27%). During follow-up there were 117 deaths or AMI. The prevalence of anaemia on admission was 20% and this figure increased to 40% at 7 weeks follow-up. Adjusting for a variety of baseline, clinical, laboratory and echocardiogaphic variables (left ventricular systolic dysfunction), the presence of anaemia was strongly associated with subsequent deaths or AMI when measured on admission (adjusted relative risk (RR) 1.73; 95% CI 1.13 to 2.66) and also at 7 weeks post-ACS (adjusted RR 1.67; 95% CI 1.04 to 2.69). Patients with persistent anaemia at 7 weeks were at an increased risk of death or AMI compared with those with persistently normal haemoglobin (unadjusted RR 3.58; 95% CI 2.04 to 6.29) (see fig). Conclusion: In ACS, the prevalence of anaemia increases substantially at 7 weeks follow-up (40%) when compared with admission haemoglobin levels. Both the presence of anaemia at baseline and at follow-up independently predicts long-term adverse clinical outcomes. Furthermore, our study suggests that the trend of haemoglobin post-ACS is a more important predictor of adverse prognosis compared with a one-off low haemoglobin level at baseline.